Fat-free mass is associated with exercise pressor responses, but not cold pressor responses, in humans: influence of maximal voluntary contraction - Stavres, Jon; Aultman, Ryan S.; Brandner, Caleb F.; Newsome, Ta’Quoris A.; Vallecillo-Bustos, Anabelle; Graybeal, Austin J. (Frontiers in Sports and Active Living, 2024)
Objective This study examined the contributions of fat mass (FM) and fat-free mass (FFM) to the magnitude of exercise pressor responses in humans. Methods The cumulative blood pressure responses (blood pressure index; BPI) to handgrip exercise (BPIhg), post-exercise-circulatory-occlusion (BPIpeco), and cold-pressor activation (BPIcpt) were collected from 67 individuals grouped by BMI (27.8 ± 7.3 kg/m2), FFM index (FFMi, 29.1 ± 3.8 kg/m2), and FM index (FMi 12.5 ± 4.8 kg/m2) quartiles. BPI responses to HG were also normalized to the time-tension index of HG, providing a relative index of exercise pressor response magnitude (BPInorm). Results BPIhg and BPIpeco were significantly elevated in the third FFMi quartile (p ≤ 0.034), while BPInorm significantly decreased in the second and fourth quartiles (p ≤ 0.029). In contrast, no differences in BPIcpt were observed across any FFMi, BMI, or FMi quartiles (p ≥ 0.268). FFM was independently associated with BPIhg, BPIpeco, and BPInorm (all p ≤ 0.049), however, FFM was eliminated as an independent predictor when maximal voluntary contraction (MVC) was included in these regression models (all p ≥ 0.495). Neither FFM nor MVC was associated with BPIcpt (p ≥ 0.229). Conclusions These findings indicate that exercise pressor responses, but not cold-pressor responses, are significantly associated with FFM in humans, and that this association is driven by FFM related differences in MVC.